Chemical quality assessment of organic cow’s milk at KPSP Setia Kawan Nongkojajar using Lactoscan® technology - Amnifu , Johan Valen Febriano; Sukariada , I Putu Juli; Puspitayani , Putu Mira (ARSHI Veterinary Letters, 2025)
Organic cow milk is produced from cows raised in natural, low-stress environments without the use of growth hormones or synthetic additives, resulting in milk with high nutritional value and safety for direct consumption. This study aimed to evaluate the quality of organic cow milk, specifically its lactose, fat, protein content, and freezing point, to ensure compliance with the Indonesian National Standard (SNI) 3141.1:2011for fresh milk. Quality testing was conducted using the Lactoscan® method on eight samples collected from different milk storage posts at the Setia Kawan Dairy Farming Cooperative in Nongkojajar, Pasuruan Regency. The analysis revealed average levels of 4.36% fat, 2.86% protein, and 4.36% lactose, all of which met or exceeded the SNI requirements for fresh cow milk. These findings affirm that the cooperative's organic milk meets the national quality standards and can be considered a nutritious and safe dairy product.